The Characteristics and Impacts of Singapore-U.S. Relations Under Prime Minister Lee Hsien Loong - Truong, Hue Thi (Center for Southeast Asian Social Studies (CESASS), 2023)
The relationship between Singapore and the United States under Prime Minister Lee Hsien Loong is marked by equality and mutual benefits, despite the imbalance of power between the small nation and the superpower. This study aims to explore the pragmatism of Singapore’s foreign policy and how it has shaped bilateral relations, leading to substantial advantages for both parties. Using a combined research approach, including the analysis of diplomatic records, policy documents, and historical data, this study examines the political, economic, and security impacts of Singapore-U.S. relations. The theoretical framework is based on small-state foreign policy theory and international relations, focusing on the strategic roles smaller countries play when engaging with larger powers. Findings reveal that Singapore’s ties with the U.S. have significantly enhanced its position in Southeast Asia, strengthened economic and security interests, and improved cooperation with ASEAN in the context of U.S. Indo-Pacific strategies. The analysis argues that Singapore’s flexible foreign policy has allowed it to leverage its partnership with the U.S. to maximize national benefits and influence broader ASEAN-U.S. relations in meaningful ways.